2023
DOI: 10.3390/ijerph20032179
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change and Land Use/Cover Change on the Net Primary Productivity of Vegetation in the Qinghai Lake Basin

Abstract: The Qinghai Lake Basin acts as a natural barrier, preventing the western desert from spreading eastward. This is an important link in preserving the ecological stability of the northeastern region of the Qinghai–Tibet Plateau (QTP). Therefore, quantitative research into the net primary productivity (NPP) of vegetation and its driving force in the Qinghai Lake Basin is required. The effects of land use/cover change (LUCC) and climate change on NPP in the Qinghai Lake Basin were studied using R-contribution rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…The results of this study revealed the presence of obvious differences in the average NPP of different land-use types in Yangzhou City from 2000 to 2020. Specifically, the values were ranked in descending order as forest > farmland > unused land > urban > water, indicating that the NPP level was related to land-use type, which is consistent with previous research results [26,39,45]. Vegetation NPP values in Yangzhou City exhibited significant temporal and spatial differentiation.…”
Section: Spatiotemporal Evolution Of Npp and Prediction Of Future Trendssupporting
confidence: 89%
See 3 more Smart Citations
“…The results of this study revealed the presence of obvious differences in the average NPP of different land-use types in Yangzhou City from 2000 to 2020. Specifically, the values were ranked in descending order as forest > farmland > unused land > urban > water, indicating that the NPP level was related to land-use type, which is consistent with previous research results [26,39,45]. Vegetation NPP values in Yangzhou City exhibited significant temporal and spatial differentiation.…”
Section: Spatiotemporal Evolution Of Npp and Prediction Of Future Trendssupporting
confidence: 89%
“…Geographical detectors were used to analyze 10 driving factors related to climate, society, and ecology. The main climate factors were temperature (TEM), rainfall, and solar radiation (RAD), which were highly correlated with vegetation growth [26]. The ecological factors were NDVI, WET, NDBSI, etc., which reflect the environmental ecological quality in the remote-sensing ecological index proposed by Xu Hanqiu [33].…”
Section: Analysis Of Factors Driving the Variation Of Vegetation Npp ...mentioning
confidence: 99%
See 2 more Smart Citations
“…With lovely weather, it is cold in winter cold and warm and cool in summer and autumn. The average temperature in January is -17.5℃ and 11℃ in July, and the annual average temperature is -0.6℃ [7]. The annual sunshine hours in Guncha County are 3037 hours, with a 68% sunshine percentage.…”
Section: Overview Of the Study Areamentioning
confidence: 99%